2015
DOI: 10.1007/s10686-015-9484-8
|View full text |Cite
|
Sign up to set email alerts
|

The EChO science case

Abstract: The discovery of almost two thousand exoplanets has revealed an unexpectedly diverse planet population. We see gas giants in few-day orbits, whole multi-planet systems within the orbit of Mercury, and new populations of planets with masses between that of the Earth and Neptune-all unknown in the Solar System. Observations to date have shown that our Solar System is certainly not representative of the general population of planets in our Milky Way. The key science questions that urgently need addressing are the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 192 publications
(371 reference statements)
0
3
0
Order By: Relevance
“…On the opposite, scattered spectra can inform us on the stability and the redundancy in the information content of Ariel spectra. Previous studies have used both types to simulate observations by future telescopes (Barstow et al 2012;Tinetti et al 2015Tinetti et al , 2018Feng et al 2016Feng et al , 2018Rocchetto et al 2016;Batalha et al 2017;Mollière et al 2017;Blumenthal et al 2018;Changeat et al 2019aChangeat et al , 2019bEdwards et al 2019b;Lustig-Yaeger et al 2019). Feng et al (2018) results predicted that the retrieved uncertainties should be similar in both scattered and unscattered runs but that the retrieved mean could be different.…”
Section: The Ability Of Ariel To Reveal Chemical Trends In Exoplanetmentioning
confidence: 99%
“…On the opposite, scattered spectra can inform us on the stability and the redundancy in the information content of Ariel spectra. Previous studies have used both types to simulate observations by future telescopes (Barstow et al 2012;Tinetti et al 2015Tinetti et al , 2018Feng et al 2016Feng et al , 2018Rocchetto et al 2016;Batalha et al 2017;Mollière et al 2017;Blumenthal et al 2018;Changeat et al 2019aChangeat et al , 2019bEdwards et al 2019b;Lustig-Yaeger et al 2019). Feng et al (2018) results predicted that the retrieved uncertainties should be similar in both scattered and unscattered runs but that the retrieved mean could be different.…”
Section: The Ability Of Ariel To Reveal Chemical Trends In Exoplanetmentioning
confidence: 99%
“…Future exoplanet characterization missions, like the proposed FINESSE, EChO, and ARIEL missions (Deroo et al 2012;Tinetti et al 2015Tinetti et al , 2016, will be able to measure spectroscopic phase curves with a high spectral resolution across a wide wavelength range from the optical to the IR. Unlike current space-based facilities (HST, Spitzer) such missions will be specifically designed for this task and will have the telescope time to measure the spectroscopic phase curve for a sample of planets.…”
Section: Multi-band Phase Curvesmentioning
confidence: 99%
“…Line et al (2013) emphasize that the second approach is invalid for most current exoplanet spectra due to their limited information content. Barstow et al (2013b,a) use optimum estimation (Irwin et al 2008) to assess the retrievability of the atmosphere of the super-Earth GJ1214b and hot Jupiters, respectively; they compared three different parameterizations and concluded that the proposed EChO space telescope (Tinetti et al 2015) should have been able to characterize the temperature of gas giants with about 200 K precision. The τ-REX (Waldmann et al 2015b) employs a two-stage hybrid approach combining the parametric and layer-by-layer representation.…”
Section: Introductionmentioning
confidence: 99%